Diabetes induces stromal remodelling and increase in chondroitin sulphate proteoglycans of the rat ventral prostate - Ribeiro, Daniele Lisboa; Taboga, Sebastiao Roberto; Goes, Rejane Maira [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
P>Extracellular matrix (ECM) remodelling is an important process involved in prostate cancer progression. Alterations in ECM caused by diabetes in different tissues such as kidney is well described; however, it is poorly investigated in prostate. The aim of this study was to evaluate changes in ECM of rat prostate showing gland atrophy caused by diabetes and their implications in development of malignant lesions. Diabetes was induced in Wistar rats using alloxan (45 mg/kg bw). After 90 days of diabetes onset, animals were killed and ventral prostate was removed and prepared for light microscopy following immunoreaction for fibronectin, chondroitin sulphate and Picrossirius staining for collagen fibres. Proteoglycans (PG) were identified at transmission electron microscopy after fixation with Cuprolinic Blue. Diabetes led to a thickening of 25% in the acinar basement membrane accompanied by increase and disorganization of its proteoglycans (P1). Three additional populations of prostatic stromal PGs were identified: collagen fibril linked (P2) and interstitial (P3) and (P4) PGs. Diabetes increased P3 and mainly P4 which had higher dimension and accumulated around the smooth muscle cells. In addition, an increase in chondrotin sulphate (33%, mainly in sites where P4 were noted) and collagen (44%) was noted in diabetic rats, whereas fibronectin did not change. Atrophic changes observed in rat ventral prostate after diabetes are accompanied by stromal remodelation related to increase in collagen and chondroitin sulphate proteoglycans. Thus, diabetes can promote a stromal microenvironment rich in elements that could favour cell migration, proliferation and pathological process.
Keywords: chodroitin sulphate; Collagen; Diabetes; Prostate; proteoglycans